LITERASI EMOSI ASPEK MAMPU MENGETAHUI PERASAAN DIRI: STUDI ETNOGRAFI KELAS V SEKOLAH DASAR - Hilda Luthfiyah; Seni Apriliya; Muhammad Rijal Wahid Muharram (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to show the urgency of the importance of emotional literacy education through the results of emotional literacy analysis research on elementary school students. Therefore, The purpose of this study is to describe the results of the analysis of emotional literacy in the aspect of knowing one's own feelings of male students at an elementary school in Tasikmalaya City. The approach in this study is qualitative with a class ethnography method with a random participant selection technique, namely grade V students and elementary school teachers. The data collection technique is through observation and interviews. The data analysis of this study is based on Steiner's emotional literacy theory, with three stages including data reduction, data presentation, and drawing conclusions. The results of this study are that elementary school students experience various emotions; only knowing their feelings without knowing how to express them properly; lack of emotional management; some students express emotions by behaving negatively both verbally and physically. It can be concluded that the emotional literacy of these male students, especially in the aspect of knowing their own feelings, is still relatively low. The implication is that education about emotional literacy is needed for elementary school students to develop skills in managing emotions.